EKSPLORASI PEMAHAMAN PEDAGOGIK GURU DALAM MENERAPKAN PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Rahmi S. Kadir; Muh. Khaerul Ummah. BK; Moh. Rudini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Rahmi S. Kadir 2025. Exploration of Teachers' Pedagogical Understanding in Implementing Differentiated Learning in Elementary Schools. Thesis, Elementary School Teacher Education, Faculty of Teacher Training and Education, Madako University. Supervisor 1: Muh. Khaerul Ummah.BK, Supervisor 2: Moh. Rudini This research is motivated by the diversity of student characteristics, interests, and learning styles that require teachers to implement differentiated learning strategies in elementary schools. This study aims to describe the implementation of differentiated learning based on teachers' pedagogical understanding and analyze the obstacles and challenges faced by teachers at SDN 21 Biau. This study used a qualitative approach with an exploratory method. Data were collected through three techniques: observation, interviews, and documentation. The results show that teachers' pedagogical understanding of differentiated learning is still limited. Teachers tend to use uniform teaching materials (content), have not fully implemented process strategies that are in accordance with students' learning styles, and product assessments are not oriented to individual student needs. The main obstacles identified include limited infrastructure, lack of technical training on the independent curriculum, the absence of a systematic initial diagnostic assessment, and the school's location far from the training center.